Investigation Of Sustainable Design Parameters In Cold And Dry Climates (Journal of Pharmaceutical Negative Results, 2022)
Sustainable development with emphasis on meeting the current needs of the general public and without threatening their future, taking into account the environment and future generations has become a prominent issue in various societies. Therefore, identifying and prioritizing the main factors of sustainable architecture according to the climatic characteristics of each region can be the first step in preserving architecture as a process.Because a large portion of greenhouse gases are emitted by the building sector, a change in approach to sustainable architecture has been made that can play a significant role in mitigating the effects of climate change. Although climate change is inevitable, adaptive architectural measures must be taken to reduce its impact. One of the goals of this article is to create an overview of sustainability and finally provide solutions in the field of architecture along with the climate issues of the cold and dry region. Also, the goal of sustainability is to create buildings that are able to withstand the cold and dry climate and to consider the necessary adaptation to the energy required for buildings with changes in the condition of this climate.The literature on this subject has been examined through a search of scientific databases. In the future, it is necessary to pay attention to the compatibility of sustainable design and how it can adapt to its climate.